Vascular degeneration and retinal remodeling in rd10 mice: correlating OCT, OCTA, and histological findings - Albertos-Arranz, Henar; Sánchez-Sáez, Xavier; Kutsyr, Oksana; Fernández-Sánchez, Laura; Sánchez-Castillo, Carla; Lax, Pedro; Cuenca, Nicolás (Frontiers in Neuroanatomy, 2025)
IntroductionIdentifying long-term changes in retinal structure and vasculature is essential for interpreting in vivo imaging techniques such as optical coherence tomography (OCT) and OCT angiography (OCTA) in retinal diseases. We characterized long-term alterations in vasculature, retinal structure, and glial cells by combining immunohistochemistry (IHC) with OCT and OCTA in a murine model of retinitis pigmentosa.MethodsTransversal retinal sections and wholemount retinas from C57BL/6J and rd10 mice, aged P20 to 24 months, were immunostained to evaluate retinal structure, glial cells, retinal pigment epithelium (RPE), and the vascular network. OCT and OCTA images from the central retina were also analyzed.ResultsSignificant retinal remodeling in the inner retina occurs over time and was detectable from 4 months using IHC and from 6 months using OCT. Remodeling was characterized by glial activation (reactive gliosis) and the formation of hyperreflective columns, which contain Müller cells, activated microglia, RPE, and choroidal vessels in the late stages. No significant differences were observed between OCTA and IHC vascular density of the superficial vascular plexus (SVP) and deep capillary plexus (DCP) in rd10 mice at any time points, except at 2 months (SVP, p = 0.009; DCP, p = 0.001). This seems a critical stage, suggesting differing rates of blood flow reduction and structural vessel loss. A peak of vascular degeneration in the SVP of rd10 mice was detected by OCTA between 2 and 6 months (p = 0.003), but not by IHC. Vascular degeneration peak of DCP in rd10 was observed between P20 and 2 months using OCTA (p < 0.0001), and between 2 and 6 months using IHC (p = 0.003).ConclusionOverall, OCTA and IHC yielded comparable long-term vascular density results, supporting OCTA as a reliable, non-invasive tool for studying vessel degeneration in animal models. Therefore, longitudinal in vivo evaluation of retinal remodeling through OCT and OCTA constitutes a valuable methodology for investigating disease mechanisms and guiding therapeutic development.